The Expression of Politeness Category in The Uzbek And English Languages - Erkinovna, Yuldasheva Feruza; Djurabaevna, Djumayeva Nozima; Askarovna, Shukurova Madina (International Journal of Psychosocial Rehabilitation, 2020)
The relevance of the study is due to the growing interest of linguists in the problems of interpersonal verbal interaction and the psychology of speech behavior of native speakers. Much attention is paid to the study of speech etiquette, the functioning of conventional phrases and the degree of their clichés, especially in cultural and comparative terms. However, these aspects are only the essence of explicit or conventional politeness (R. Ratmayr). Implicit or individual politeness, consisting in respecting the maxim of politeness, implemented by various strategies of courtesy and diplomacy, has not been studied enough and, undoubtedly, should be the object of closer attention of linguists.